Genetic Alterations in Esophageal Tissues From Squamous Dysplasia to Carcinoma - Liu, Xi; Zhang, Min; Ying, Songmin; Zhang, Chong; Lin, Runhua; Zheng, Jiaxuan; Zhang, Guohong; Tian, Dongping; Guo, Yi; Du, Caiwen; Chen, Yuping; Chen, Shaobin; et al. (Gastroenterology (New York, N.Y. 1943), 2017)
Esophageal squamous cell carcinoma (ESCC) is the most common subtype of esophageal cancer. Little is known about the genetic changes that occur in esophageal cells during the development of ESCC. We performed next-generation sequence analyses of esophageal nontumor, intraepithelial neoplasia (IEN), and ESCC tissues from the same patients to track genetic changes during tumor development. We performed whole-genome, whole-exome, or targeted sequence analyses of 227 esophageal tissue samples from 70 patients with ESCC undergoing resection at Shantou University Medical College in China from 2012 through 2015 (no patients had received chemotherapy or radiation therapy); we analyzed normal tissues, tissues with simple hyperplasia, dysplastic tissues (IEN), and ESCC tissues collected from different regions of the esophagus at the same time. We also obtained 1191 nontumor esophageal biopsy specimens from the Chaoshan region (a high-risk region for ESCC) of China (a high-risk region for ESCC) and performed immunohistochemical and histologic analyses to detect inflammation. IEN and ESCC tissues had similar mutations and copy number alterations, at similar frequencies; these differed from mutations detected in tissues with simple hyperplasia. IEN tissues had mutations associated with apolipoprotein B messenger RNA editing enzyme, catalytic polypeptide-like–mediated mutagenesis (a DNA damage mutational signature). Genetic analyses indicated that most ESCCs were formed from early stage IEN clones. Trunk mutations (mutations shared by >10% of paired IEN and ESCC tissues) were in genes that regulate DNA repair and cell apoptosis, proliferation and adhesion. Mutations in TP53 and CDKN2A and copy number alterations in 11q (contains CCND1), 3q (contains SOX2), 2q (contains NFE2L2), and 9p (contains CDKN2A) were considered to be trunk variants; these were dominant mutations detected at high frequencies in clones of paired IEN and ESCC samples. In the esophageal biopsy samples from high-risk individuals (residing in the Chaoshan region), 68.9% had an evidence of chronic inflammation; the level of inflammation was correlated with atypical cell structures and markers of DNA damage. We analyzed mutations and gene copy number changes in nontumor, IEN, and ESCC samples, collected from 70 patients. IEN and ESCCs each had similar mutations and markers of genomic instability, including apolipoprotein B messenger RNA editing enzyme, catalytic polypeptide-like. Genomic changes observed in precancerous lesions might be used to identify patients at risk for ESCC.